Hukum Menggugurkan Kandungan dan Membekalkan Bahan Konstraseptif kepada Penzina Remaja dari Perspektif Islam - Ab. Ghani, Anisah (Jurnal Fiqh, 2009)
The statistic of the cases of pregnancy out marriage among the youngsters shows a frightening increase in the recent years. The Muslims doctors who have to face the pregnant youngsters as their patient are in a very difficult situation in making decision between prescribing to them the contraceptive pills or not. Both are having their own expected consequences. To prescribe contraceptive pills in tantamount to permit adultery to happen and avoiding it will lead to crimes such as illegal abortion and disowning or killing newborn babies as recently being reported in news quite often. This article attempts to give light to this issue from islamic point of view by discussing the islamic perspective on abortion and to give some ideas on the issue of prescribing contraceptive pills to the above youngsters.